2020
DOI: 10.1002/jocb.463
|View full text |Cite
|
Sign up to set email alerts
|

Social Environmental Factors and Personal Motivational Factors Associated with Creative Achievement: A Cross‐Cultural Perspective

Abstract: Although the theory of the socio‐cultural approach to creativity is gaining steam, empirical studies with advanced statistical tools are lagging behind. To address the gap of empirical studies integrating individual, social environmental, and cultural factors, we examined how motivational factors and environmental responsiveness were jointly related to college students’ creative achievement in different nations. Participants were university students from eight culturally and geographically diverse regions: Arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 88 publications
2
17
0
Order By: Relevance
“…The present study selected the parental responsiveness subscale from the Parenting Style Inventory II (Darling and Toyokawa, 1997). We translated this English version subscale into the Chinese version scale, which was also used in a previous study (Zhang et al, 2021). The original subscale consists of five items (e.g., "My most influential parent and I do things that are fun together").…”
Section: Parental Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study selected the parental responsiveness subscale from the Parenting Style Inventory II (Darling and Toyokawa, 1997). We translated this English version subscale into the Chinese version scale, which was also used in a previous study (Zhang et al, 2021). The original subscale consists of five items (e.g., "My most influential parent and I do things that are fun together").…”
Section: Parental Responsivenessmentioning
confidence: 99%
“…For the present study, we selected the Lecture Responsiveness Scale adapted by Zhang et al (2021) to measure teaching responsiveness. The original scale consists of five items and uses a 6-point Likert scale.…”
Section: Teaching Responsivenessmentioning
confidence: 99%
“…Most of the research on the motivational function of implicit theories of creativity exists within the branch of the creative mindset (Karwowski & Brzeski, 2017; Karwowski & Kaufman, 2017). Specifically, a growing body of empirical studies now underscores the association between creative growth mindset and various motivational aspects of creative behaviors (for a review, see Zhang et al, 2019) . It implies that a creative growth mindset carries out motivational functions.…”
Section: Figurementioning
confidence: 99%
“…Similarly, creative growth was made possible in newcomers when trust in leadership was rated as high in the workplace ( Harris et al, 2013 ). In the classroom, teachers instilling trust by showing respect, care and tolerance for differences ( Richardson and Mishra, 2018 ) as well as responsiveness (i.e., warmth or support; Zhang et al, 2020 ), were found to facilitate creative behaviors in students.…”
Section: The Creative Potential Elementsmentioning
confidence: 99%